Communicating The Cultural Values by Vloggers in Disruption Era - Wahyuningtyas, Bhernadetta Pravita; Zulqarnain, Wajid (Universitas Semarang, 2024)
Introduction: In the age of digital transformation, the role of vloggers in shaping and communicating cultural values has become increasingly significant. This paper explores how vloggers navigate the complexities of cultural representation in the era of disruption, characterized by rapid technological advancements, shifting social dynamics, and global interconnectedness. It emphasizes the role of vloggers as both creators and influencers, who, through their personal stories and interactions with their audiences, contribute to the evolving discourse on cultural values, particularly in relation to issues such as authenticity, diversity, and social change. Methods: The study utilized a constructivism paradigm with a phenomenological approach to popular vloggers in Indonesia. Data collection techniques: in-depth interviews, observation, literature studies, and triangulation of data sources. The validity of the qualitative research data was determined through credibility, transferability, dependability, and confirmability. Findings: Communicating the cultural values play a crucial role in intercultural communication, as they are deeply connected to personal beliefs and ways of living. Understanding and acknowledging these personal values are essential for successful communication, especially when individuals come from different cultural backgrounds. Failure to recognize and respect these differences in values can lead to significant challenges in communication and understanding. Originality: The study highlights the emerging role of vloggers as cultural architects, rather than merely content creators, they are not passive communicators but an active agent of social change. Many vloggers use their platforms to advocate for social justice, equality, demonstrating how vloggers contribute to societal shifts and cultural reimagination.